2002
DOI: 10.1007/s003400200796
|View full text |Cite
|
Sign up to set email alerts
|

High-energy ion generation in interaction. of short laser pulse with high-density plasma

Abstract: Sentoku, Y.; Bychenkov, V. Y.; Flippo, K.; Maksimchuk, Anatoly; Mima, K.; Mourou, G.; Sheng, Z. M.; and Umstadter, Donald, "Highenergy ion generation in interaction of short laser pulse with high-density plasma" (2002). Donald Umstadter Publications. 76.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
81
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(91 citation statements)
references
References 31 publications
(82 reference statements)
9
81
0
1
Order By: Relevance
“…Both experiments [10,11] and simulations [12] have demonstrated an increase of ion energy with a corresponding reduction of the target thickness. The high contrast pulses of modern lasers [10,11] have enabled effective acceleration of ions from ultrathin foils that are semitransparent to laser light.…”
Section: Introductionmentioning
confidence: 91%
“…Both experiments [10,11] and simulations [12] have demonstrated an increase of ion energy with a corresponding reduction of the target thickness. The high contrast pulses of modern lasers [10,11] have enabled effective acceleration of ions from ultrathin foils that are semitransparent to laser light.…”
Section: Introductionmentioning
confidence: 91%
“…Given the experimental data, one may refer to T c ~ 1-2 keV and T h ~ 1-10 MeV as the typical values. For short laser pulses of relativistic intensity, the hot electron temperature scales with a laser intensity quite close to the dependence [51][52][53], so that the parameter T h in our approach can serve as a connecting link to the laser, together with the number of hot electrons, n h , which depends on the laser pulse energy rather than its intensity. Considering T h and n h as the controlling laser parameters, we aim to characterize the ion acceleration that depends on them and on the parameters of a plasma such as its thickness, temperature, and ion composition.…”
Section: High-energy Ion Generation By Short Laser Pulses 485mentioning
confidence: 80%
“…Stochastic heating originates from the standing wave formation due to the reflection of laser light. This was proved by the simple numeric model presented in [52], where it was shown that stochastic electron heating occurs when r > 0.2.…”
Section: Particle Acceleration In Pic Simulationsmentioning
confidence: 86%
See 1 more Smart Citation
“…For instance, when an intense laser pulse interacts with a solid-density target, it is partially reflected, and the beating between the incident and reflected light in the underdense plasma region will create interference, which can modify the optical properties of the plasma [2], excite plasma waves [3], and heat electrons [4]. It has been suggested theoretically [5] that this stochastic heating of electrons is ultimately responsible for the acceleration of multi-MeV energy beams of ions from laser-irradiated thin foils [6 -8]. In inertial fusion research, the electron heating and modification of the laser reflectivity that results from crossed laser beams [9][10][11][12] must be controlled in order to efficiently couple energy to the fusion target.…”
mentioning
confidence: 99%